Physiological characteristics and yield of ‘Pérola’ pineapple in the semi-arid region - Cleiton F. B. Brito; Marcelo R. dos Santos; Varley A. Fonseca; Alessandro de M. Arantes; Jean R. de Almeida (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the physiological characteristics and yield of ‘Pérola’ pineapple subjected to irrigation with saline water in the semi-arid region of Bahia. The experiment was conducted in randomized blocks with five treatments, represented by irrigation depths: 100% ETc, using water with electrical conductivity (ECw) of 0.75 dS m-1, and 50, 75, 100 and 125% ETc, using water with ECw of 3.6 dS m-1. The experiment used a drip irrigation system and pressure-compensating emitters with a discharge of 8 L h-1. In the physiographic conditions of Guanambi-BA, pineapple has limitations of the physiological characteristics of chlorophyll fluorescence and chlorophyll index, under irrigation with both saline water and better-quality water. The irrigation depth corresponding to 100% ETc using water with ECw levels of 0.75 and 3.6 dS m-1 led to the best yields.